Preparation method of carbon-doped boron nitride catalyst and application of carbon-doped boron nitride catalyst in synthesis of vinyl chloride through acetylene hydrochlorination

By preparing carbon-doped boron nitride catalysts, the problems of high cost, inactivation and pollution of existing catalysts have been solved, and the catalytic effect of efficient and environmentally friendly acetylene hydrochloride synthesis of vinyl chloride is achieved, with broad industrial application prospects.

CN119608200AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311175442.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing catalysts for synthesis of vinyl chloride by acetylene hydrochloride, such as gold-based catalysts, have high costs, catalyst deactivation and environmental pollution. The catalytic performance of non-precious metal catalysts is also low, and the stability of most non-metal catalysts is insufficient.

Method used

A catalyst with a high specific surface area and a controlled carbon content is prepared by mixing, drying, calcining and vapor deposition (CVD) treatment steps.

Benefits of technology

The catalyst is cheap, has excellent performance, is completely free of mercury, has high conversion rate and selectivity, and has a stability of more than 400 hours. It is suitable for industrial applications, and has a simple and environmentally friendly process and is easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608200A_ABST
    Figure CN119608200A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon-doped boron nitride catalyst and application of the carbon-doped boron nitride catalyst in synthesis of vinyl chloride through acetylene hydrochlorination. Comprising the following steps: 1) dissolving a boron source and a nitrogen source in a solvent to prepare a mixed solution; 2) heating, drying and calcining the solution obtained in the step 1) to obtain a porous boron nitride precursor; and 3) introducing a carbon source, and carrying out CVD treatment on the precursor obtained in the step 2) to obtain the carbon-doped boron nitride catalyst. The carbon-doped boron nitride catalyst disclosed by the invention can be applied to acetylene hydrochlorination to prepare and synthesize vinyl chloride, the conversion per pass of acetylene is 88.4% or above, the selectivity of vinyl chloride is 99.2% or above, and the service life can reach 400 hours or above. The method has the characteristics of simple and environment-friendly catalyst preparation process, low cost, excellent performance, small industrialization difficulty, good process repeatability and the like, is expected to replace a mercury catalyst in the existing calcium carbide process, and solves the problem of mercury emission pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the preparation of vinyl chloride by acetylene hydrochlorination, and specifically relates to a preparation method of a carbon-doped boron nitride catalyst and application thereof in the synthesis of vinyl chloride by acetylene hydrochlorination. Background Art

[0002] The production process of polyvinyl chloride plastic (PVC) is the polymerization of vinyl chloride monomer (VCM), which can be obtained by ethylene method, acetylene method and ethane method. Due to the basic national conditions of rich coal, poor oil and little gas, the existing industrial process in China is mainly coal-based acetylene method, that is, electrophilic addition of coal-based acetylene and hydrogen chloride in the presence of catalyst. Industrially, the 10wt.% mercuric chloride / activated carbon catalyst (HgCl2 / AC) used in the acetylene method of vinyl chloride production process has high reactivity and selectivity, as well as good reaction stability, but the loss of catalyst Hg leads to obvious catalyst deactivation and brings huge pollution to the environment.

[0003] One of the main problems with gold-based catalysts is that gold ions are easily reduced to inactive gold nanoparticles during the reaction, and this is accompanied by the sintering problem of the nanoparticles. The second problem is that the high price of gold leads to high costs, which limits the industrialization of gold catalysts. Although many researchers are currently increasing efficiency and reducing costs through surface modification of activated carbon carriers, such as introducing surface functional groups and doping heteroatoms, constructing surface defect sites, adding ionic liquids or additives and ligand modification, and single-atom dispersion, there is still a certain distance from industrial application at this stage.

[0004] For non-precious metal catalysts such as tin, bismuth, copper, cobalt and other metal catalysts, their metal prices are relatively low, but their catalytic activity is significantly lower than that of precious metal catalysts. Currently, researchers have used strategies such as increasing the metal loading, loading metal catalysts after carrier modification, and ligand-modified metal catalysts to improve the reaction performance of catalysts, but the catalytic performance of non-precious metal catalysts is still far behind that of precious metal catalysts.

[0005] Non-metallic catalysts, relying on good performance and low cost, provide a new path for the mercury-free production of acetylene hydrochlorination. With the deepening of research, the reaction activity and stability of non-metallic catalysts are also steadily improving, and some results are comparable to those of precious metal catalysts. However, the stability of most non-metallic catalysts still needs to be improved. Among the reported non-metallic catalysts, porous boron nitride has achieved excellent performance, but the required temperature is too high and the intrinsic activity is poor. Therefore, the introduction of carbon by doping method is expected to further optimize the catalytic ability of boron nitride catalyst in acetylene hydrochlorination reaction.

[0006] The current technology for preparing carbon-doped boron nitride mainly includes precursor pyrolysis, template method, chemical vapor deposition method, molten salt method, etc. For the precursor pyrolysis method, that is, by preparing a boron source, a carbon source, and a nitrogen source into a precursor, carbon-doped boron nitride can be directly prepared in one step by high-temperature calcination. However, since the carbon source and the nitrogen source will decompose together during the calcination process to release highly toxic and harmful gases such as (CN)2, HCN and NH3, the scale application of this synthesis method is seriously limited. For the template method, the template method for preparing BCN nanomaterials is to use C-containing materials such as nanotubes, nanowires and nanosheets as templates, and B and N atoms replace part of the C atoms in the template through reaction to obtain BCN nanomaterials. However, when synthesizing BCN nanomaterials using the template method, a small amount of carbon often remains between the lattice layers, resulting in low purity, and the subsequent process of removing the template agent is complicated. Chemical vapor deposition (CVD) is one of the main methods for preparing BCN thin film materials. This method is to pass gaseous reactants into the reactor, and through chemical reactions, solid phase substances are deposited on the substrate. This method can obtain BCN coatings or BCN thin film materials with high purity, but it is impossible to prepare porous structures and it is difficult to achieve large-scale preparation. The molten salt method for preparing BCN nanomaterials is to disperse raw materials such as boric acid, glucose and urea into a low-melting salt system. The low-melting salt acts as a reaction medium to provide a liquid environment for the raw materials at a certain temperature to achieve uniform mixing of the raw materials at the molecular level or atomic size. This method requires a large amount of solvent for washing in the later stage, and the process is complicated. Like the precursor pyrolysis method, it will release toxic gases. Summary of the invention

[0007] In view of the above problems, the present invention provides a method for preparing a carbon-doped boron nitride catalyst and its application in the synthesis of vinyl chloride by acetylene hydrochlorination. The catalyst has the characteristics of simple and environmentally friendly preparation process, low cost, superior performance, low industrialization difficulty, good process repeatability, etc., and is very likely to replace the current mercury-based catalyst of the calcium carbide process.

[0008] In order to achieve the above object, the technical solution of the present invention is as follows:

[0009] In one aspect, the present invention provides a method for preparing a carbon-doped boron nitride catalyst, the method comprising the following steps:

[0010] 1) Mixing: heating in an oil bath, dissolving the boron source and the nitrogen source in a mixed solvent of ethanol and water to obtain a mixed solution;

[0011] 2) Drying: drying the mixed solution obtained in step 1) to obtain a precursor;

[0012] 3) Calcination: calcining the precursor obtained in step 2) under an inert atmosphere to obtain a boron nitride precursor;

[0013] 4) CVD treatment: The boron nitride precursor obtained in step 3) is introduced into a carbon source for CVD treatment to obtain the carbon-doped boron nitride catalyst.

[0014] In the above technical scheme, further, in the step 1), the oil bath temperature is 60-90°C; the boron source includes one or two of boric acid and boron oxide; the nitrogen source includes one or more of urea, dicyandiamide, melamine, biuret, dimethylguanidine and various amino acids; the boron content in the mixed solution is 30-45wt%, and the nitrogen content is 30-45wt%; the volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1-4:1.

[0015] In the above technical solution, further, in the step 2), the drying temperature is between 120 and 150°C.

[0016] In the above technical solution, further, in the step 3), the inert atmosphere is at least one of nitrogen, helium, argon, krypton and xenon; the calcination temperature is 1000° C. and the calcination time is 10 h.

[0017] In the above technical solution, further, in the step 4), the temperature of the CVD treatment is 800°C and the time is 3 to 6 hours; the carbon source is methanol, ethanol, propanol, butanol, isopropanol, isobutanol, acetonitrile, and a molecular formula of C n H 2n+2 (1≤n≤5), C n H 2n-2 (2≤n≤5) and C n H 2n One or more of the low-carbon hydrocarbons (2≤n≤5).

[0018] Another aspect of the present invention provides a carbon-doped boron nitride catalyst prepared by the above preparation method.

[0019] In another aspect, the present invention provides an application of the carbon-doped boron nitride catalyst in preparing vinyl chloride by hydrochlorination of acetylene.

[0020] In the above technical solution, further, the hydrogen chloride and acetylene raw gas after drying and dehydration are introduced into a gas-solid phase catalytic reactor carrying a carbon-doped boron nitride catalyst for reaction.

[0021] In the above technical scheme, further, the volume ratio of hydrogen chloride to acetylene is 1.4:1.0-0.6:1.0; the reaction temperature is 140-240°C; the reaction space velocity is 30-60h -1 ; The reaction pressure is normal pressure.

[0022] The beneficial effects of the present invention are:

[0023] (1) The catalyst prepared by the method provided by the present invention has a low preparation cost compared to expensive gold-based catalysts and is more suitable for current market demand; the prepared carbon-doped boron nitride catalyst has a high specific surface area and a controllable carbon content.

[0024] (2) The catalyst prepared by the method provided by the present invention is completely mercury-free, thereby solving the defects of existing industrial low-mercury activated carbon catalysts such as mercury emission pollution and catalyst deactivation due to accidental cessation of hydrogen chloride gas, showing good application prospects.

[0025] (3) The preparation method provided by the present invention is to incorporate carbon through a gaseous carbon source after high-temperature calcination, which can avoid the release of highly toxic or harmful gases such as (CN)2, HCN and NH3 in the one-step calcination method, and is safer and more environmentally friendly. Compared with the methods of the prior art, the method of the present invention is easy to prepare in large quantities and easy to achieve large-scale production.

[0026] (4) The carbon sources used in the preparation method provided by the present invention, such as methane, methanol and other gaseous carbon sources, are abundant in reserves and low in cost.

[0027] (5) The catalyst prepared by the method provided by the present invention has a wide temperature application range in the acetylene hydrochlorination process, has excellent catalytic performance at 140-240°C, has a high conversion rate (>88.4%) and selectivity for vinyl chloride (>99.2%), high stability (>400h), and requires a lower reaction temperature, which can save a lot of energy, making it have broad prospects for industrial application.

[0028] (6) The catalyst prepared by the method provided by the present invention has a higher intrinsic activity when used in the acetylene hydrochlorination process. If the intrinsic activity is too poor, the addition reaction between acetylene and hydrogen chloride cannot be carried out in time, and the adsorbed acetylene will polymerize, which will turn into carbon deposits and cause deactivation. However, when the intrinsic activity is improved, the adsorbed acetylene can react with hydrogen chloride in time, will not polymerize itself, will not be deactivated by carbon deposits, and thus the stability of the catalyst is improved (>400h). BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the XPS spectrum of BCN-AN-1 in Example 2;

[0030] Figure 2 The nitrogen physical adsorption results of BCN-AN-1 in Example 6;

[0031] Figure 3 This is the stability test result of BCN-AN-1 in Example 2. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, but the scope of the claims of the present invention is not limited by these embodiments. At the same time, the embodiments only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose.

[0033] The carbon content of the samples can be tested by X-ray photoelectron spectroscopy.

[0034] The specific surface area of ​​the sample can be tested by nitrogen physical adsorption method.

[0035] The raw materials used in the following examples are all conventional products that can be obtained commercially. The evaluation of the catalysts is carried out in a continuous online gas-solid phase reactor. A typical evaluation process is to weigh 1.00 g of catalyst, purge and dry it with argon at 120°C for 0.5 h, introduce the reaction gas at 140-240°C to start the reaction, and the product is detected by Agilent gas chromatograph 7890B, equipped with a FID detector, and the chromatographic column used is PLOT Q, which has good separation and detection performance for the gas components involved.

[0036] Example 1

[0037] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid and dissolve it in a mixed solution of 200 ml of water and 400 ml of ethanol. Heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of ground melamine powder and gradually add it to the solution with vigorous stirring.

[0038] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0039] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is helium, the calcination temperature is 1000°C, and the time is 10 hours.

[0040] (3) CVD treatment: Use inert gas to bubble liquid methanol with a flow rate of 30 ml / min, and perform CVD treatment on the solid obtained in (2) at a treatment temperature of 800° C. for 3 to 6 h.

[0041] The specific samples, their preparation conditions and carbon contents are shown in Table 1. In the table, BN-1 is a porous boron nitride with low carbon content obtained by the above method but without CVD treatment.

[0042] Table 1 Preparation and parameter performance of carbon-doped boron nitride materials

[0043]

[0044]

[0045] Example 2

[0046] (1) Liquid Phase Synthesis Synthesis Precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 400 ml of ethanol, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground melamine powder, gradually add it into the above solution, and stir vigorously;

[0047] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0048] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is argon, the calcination temperature is 1000°C, and the time is 10 hours.

[0049] (3) CVD treatment: Use inert gas to bubble liquid acetonitrile with a flow rate of 30 ml / min, and perform CVD treatment on the solid obtained in (2) at a treatment temperature of 800° C. for 3 to 6 h.

[0050] The specific samples, their preparation conditions and carbon contents are shown in Table 2.

[0051] Table 2 Preparation and parameter performance of carbon-doped boron nitride materials

[0052] Sample No. CVD processing time / h Carbon content / mass fraction% BCN-AN-1 3 13.25 BCN-AN-2 6 16.77

[0053] Example 3

[0054] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 200 ml of water and 400 ml of ethanol, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of finely ground dicyandiamide powder and gradually add it to the above solution with vigorous stirring;

[0055] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0056] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is helium, the calcination temperature is 1000°C, and the time is 10 hours.

[0057] (3) CVD treatment: using methane with a flow rate of 30 ml / min, the solid obtained in (2) was subjected to CVD treatment at a temperature of 800° C. for 3 to 6 h.

[0058] The specific samples, their preparation conditions and carbon contents are shown in Table 3.

[0059] Table 3 Preparation and parameter performance of carbon-doped boron nitride materials

[0060] Sample No. CVD processing time / h Carbon content / mass fraction% <![CDATA[BCN-CH4-1]]> 3 14.53 <![CDATA[BCN-CH4-2]]> 6 21.68

[0061] Example 4

[0062] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid and boron oxide into a mixed solution of 400 ml of water and 400 ml of ethanol, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of finely ground urea powder and gradually add it to the above solution with vigorous stirring;

[0063] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0064] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is helium, the calcination temperature is 1000°C, and the time is 10 hours.

[0065] (3) CVD treatment: using ethylene with a flow rate of 30 ml / min, the solid obtained in (2) was subjected to CVD treatment at a temperature of 800° C. for 3 to 6 h.

[0066] The specific samples, their preparation conditions and carbon contents are shown in Table 4.

[0067] Table 4 Preparation and parameter performance of carbon-doped boron nitride materials

[0068] Sample No. CVD processing time / h Carbon content / mass fraction% <![CDATA[BCN-C2H4-1]]> 3 16.43 <![CDATA[BCN-C2H4-2]]> 6 24.62

[0069] Example 5

[0070] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 400 ml of ethanol, heat and stir at 90°C until the boric acid dissolves. Then weigh 33.63 g of ground melamine powder, gradually add it into the above solution, and stir vigorously;

[0071] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0072] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is argon, the calcination temperature is 1000°C, and the time is 10 hours.

[0073] (3) CVD treatment: Use inert gas to bubble liquid ethanol, control the flow rate to 30 ml / min, and perform CVD treatment on the solid obtained in (2) at a treatment temperature of 800° C. for 3 to 6 h.

[0074] The specific samples, their preparation conditions and carbon contents are shown in Table 5.

[0075] Table 5 Preparation and parameter performance of carbon-doped boron nitride materials

[0076] Sample No. CVD processing time / h Carbon content / mass fraction% BCN-EtOH-1 3 15.16 BCN-EtOH-2 6 20.38

[0077] Example 6

[0078] (1) Liquid-phase synthesis precursor: Weigh 65.96 g of boric acid into a mixed solution of 400 ml of water and 400 ml of ethanol, heat and stir at 90°C until the boric acid dissolves, then weigh 33.63 g of ground melamine powder, gradually add it into the above solution, and stir vigorously;

[0079] Stir vigorously for 12 h in the sealed state, then evaporate the solvent at 120 °C to obtain a white powder, and the liquid phase synthesis step is completed;

[0080] (2) Calcination: After the product obtained above is dried at 120°C in air, it is calcined in an inert atmosphere to obtain a porous boron nitride material. The inert gas is helium, the calcination temperature is 1000°C, and the calcination time is 10 hours;

[0081] (3) CVD treatment: using acetylene with a flow rate of 30 ml / min, the solid obtained in (2) was subjected to CVD treatment at a temperature of 800° C. for 3 to 6 h.

[0082] The specific samples, their preparation conditions and carbon contents are shown in Table 6.

[0083] Table 6 Preparation and parameter performance of carbon-doped boron nitride materials

[0084] Sample No. CVD processing time / h Carbon content / mass fraction% <![CDATA[BCN-C2H4-1]]> 3 18.97 <![CDATA[BCN-C2H4-2]]> 6 25.38

[0085] Application Example 1

[0086] The fixed bed reaction is used as an example, but the catalyst is also suitable for moving bed reactors. The device is equipped with a gas mass flow meter and an online product analysis chromatograph (the tail gas of the reactor is directly connected to the quantitative valve of the chromatograph for periodic real-time sampling and analysis).

[0087] A typical evaluation process is to weigh 1.00g of catalyst, dry it with argon purge at 120℃ for 0.5h, introduce the reaction gas at 180-240℃ to start the reaction, and detect the product by Agilent gas chromatograph 7890B equipped with FID detector. The chromatographic column used is PLOT Q, which has good separation and detection performance for the gas components involved.

[0088] The reaction performance can be changed by changing the temperature, space velocity and the molar ratio of C2H2 / HCl in the reaction gas. The conversion rate of acetylene can reach 88.4-99.7% and the selectivity can reach 99.2-99.9%. Table 7 lists the specific applications of the catalyst and its effect data.

[0089] Table 7 Specific application of catalyst and its effect data

[0090]

[0091]

[0092] From the table above, we can see that different raw materials and different CVD processing conditions directly affect the carbon content of carbon-doped boron nitride materials, which further affects the conversion rate of acetylene and the selectivity of vinyl chloride. Compared with BN without CVD carbon doping, its conversion rate is only 38.2%.

[0093] Result analysis:

[0094] Figure 1 This is the XPS spectrum of BCN-AN-1 in Example 2, and the results show that a carbon-doped boron nitride catalyst is successfully obtained through the current synthesis method.

[0095] Figure 2 The nitrogen physical adsorption result of BCN-C2H4-1 in Example 6 shows that the catalyst has 1274m 2 / g ultra-high specific surface area.

[0096] Figure 3 The stability test results of BCN-AN-1 in Example 2 are shown in Table 2. Under the conditions of GHSV C2H2 =30h -1 , 180 ° C, C2H2 / HCl molar ratio = 1.2, the stability of Example 2 catalyst BCN-AN-1 was tested. Figure 3 It can be seen that the catalyst maintained good stability within 400 h, and both the conversion rate and conversion efficiency remained above 99%.

[0097] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a carbon-doped boron nitride catalyst, characterized in that: The method comprises the following steps: 1) Mixing: heating in an oil bath, dissolving the boron source and the nitrogen source in a mixed solvent of ethanol and water to obtain a mixed solution; 2) Drying: drying the mixed solution obtained in step 1) to obtain a precursor; 3) Calcination: calcining the precursor obtained in step 2) under an inert atmosphere to obtain a boron nitride precursor; 4) CVD treatment: The boron nitride precursor obtained in step 3) is introduced into a carbon source for CVD treatment to obtain the carbon-doped boron nitride catalyst.

2. The preparation method according to claim 1, characterized in that: In the step 1), The oil bath temperature is between 60°C and 90°C; The boron source includes one or both of boric acid and boric oxide; the nitrogen source includes one or more of urea, dicyandiamide, melamine, biuret, dimethylguanidine and various amino acids; The boron content in the mixed solution is 30-45wt%, and the nitrogen content is 30-45wt%; The volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1 to 4:

1.

3. The preparation method according to claim 1, characterized in that: In the step 2), the drying temperature is between 120°C and 150°C.

4. The preparation method according to claim 1, characterized in that: In the step 3), the inert atmosphere is at least one of nitrogen, helium, argon, krypton and xenon; the calcination temperature is 1000° C. and the calcination time is 10 hours.

5. The preparation method according to claim 1, characterized in that: In the step 4), the temperature of the CVD treatment is 800° C. and the time is 3 to 6 hours; The carbon sources are methanol, ethanol, propanol, butanol, isopropanol, isobutanol, acetonitrile, and n H 2n+2 (1≤n≤5), C n H 2n-2 (2≤n≤5) and C n H 2n One or more of the low-carbon hydrocarbons (2≤n≤5).

6. A carbon-doped boron nitride catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the carbon-doped boron nitride catalyst according to claim 6 in preparing vinyl chloride by hydrochlorination of acetylene.

8. The use according to claim 7, characterized in that: The hydrogen chloride and acetylene raw gas after drying and dehydration are introduced into a gas-solid phase catalytic reactor carrying a carbon-doped boron nitride catalyst for reaction.

9. The use according to claim 8, characterized in that: The volume ratio of hydrogen chloride to acetylene is 1.4:1.0~0.6:1.0; the reaction temperature is 140~240℃; the reaction space velocity is 30~60h -1 ; The reaction pressure is normal pressure.

Citation Information

Patent Citations

  • Boron nitride catalyst for light alkane or alkylbenzene oxydehydrogenation and preparing method and application thereof

    CN106140240A

  • Non-metal boron nitride catalyst, preparation method, applications and regeneration method thereof

    CN108187712A

  • Supported carbon catalyst preparation method

    CN109926079A

  • Non-split-phase boron-carbon-nitrogen photocatalytic material and preparation method thereof

    CN113976163A

  • Method for preparing nitrogen-doped microporous carbon material through simulated vapor deposition method and application of nitrogen-doped microporous carbon material

    CN115784194A